Invest to save: provision of a medicines management service. Issue 10 (22nd May 2013) - Bevan, Beryl; Ibrahim, Mohammed; Lane, Vanessa
Abstract The authors describe an invest‐to‐save scheme involving three London PCTs with the aim of saving between £5 and £7 for every £1 invested in pharmacists working in practices to make savings on prescribing.